Experimental study on fire spread over discrete fuel bed-Part I: Effects of packing ratio. (December 2021) - He, Qianqian; Liu, Naian; Xie, Xiaodong; Zhang, Linhe; Zhang, Yang; Yan, Weidong
Abstract: The fuel packing ratio ( β ) significantly influences the fire spread in discrete fuels; however, the underlying mechanism remains unclear. This study performed experiments using laser-cut cardboards with different packing ratios to explore the heat transfer in fire spread. We identify two distinct spread behaviors under varying packing ratios. Heat flux data indicate that radiation controls the surface heat transfer (denoting the heat transfer received by the fuel bed surface) far from the flame, while convective heating plays a considerable part surrounding the flame. The surface heat transfer is enhanced under lower packing ratios (Stage 1) and is responsible for the increase of the rate of spread (ROS) in this stage. Under higher packing ratios (Stage 2), the surface heat transfer does not vary significantly, and the surface radiation transfers more energy to fuels than surface convection. ROS reduction in Stage 2 is attributed mainly to the internal heat transfer (denoting the heat transfer received by the sides of the fuel particles) dominated by radiation. The dense fuel bed impedes the response of in-bed fuel to internal heat transfer, which, however, does not significantly influence the time integral of the internal total and radiant heat fluxes. Besides, the flame residence time almost linearly increases with the packing ratio when the flame can spread.